Historia de vida de Javier Lozano Triana, bailarín, coreógrafo y gestor cultural en el departamento de Cundinamarca (2022)
This degree work will be designed to give a chronological account of my experience in folk dance, within a methodological practice which has not only been the basis of my knowledge but has also helped my successors in training schools from the year 2000 to the present day. This document collects the cross/parallel data of my life story, using an explanatory/descriptive methodology for which information will be collected through interviews and stories. the investigation of my life story will expose in a timeline the significant experiences of my role as a dancer, trainer, and manager.